Communicative Competence Development in Teaching Foreign Language for Professional Purpose - Normurodovna, Abdirakhimova Mokhigul (Researchparks Publishing, 2023)
This article discusses general trends in the teaching of foreign languages, the principles and practices of developing professional, communicative, and intercultural competences, and the method of teaching a foreign language for professional purposes in engineering, economics, and other non-linguistic specialties. Pedagogical technology, its essence, structural components, understanding of innovative components of professional activity, and requirements for the design and engineering of pedagogical technologies are also covered. It also examines pedagogical values, the construction of the pedagogical process, communication and behavior, and pedagogical technology.